Analysis of the Impact of Value Added in the Manufacturing Industry on Economic Growth in Indonesia - Safar Nasir, Muhammad; Suripto (UMSurabaya Publishing, 2025)
This study investigates the impact of specific factors on Indonesia's economic growth across different time frames using the ARDL analysis model in Eviews 10 software. The research reveals that in the long term, increases in value added from the manufacturing sector and foreign direct investment are associated with positive and notable effects on economic growth. In the short term, enhancements in manufacturing value-added, government expenditure, population growth, and foreign direct investment contribute positively and significantly to economic growth. Conversely, inflation negatively influences economic growth in the short term. These findings are instrumental in comprehending Indonesia's economic growth drivers and provide valuable insights for policymakers and stakeholders aiming to devise effective strategies to foster economic development